optimisation OF THE FORM OF AMNESTY - Kokotova Darya (Электронное приложение к Российскому юридическому журналу, 2019)
The article considers the traditional form of amnesty in Russia, which is granted by adopting two acts (an enactment on amnesty and an enactment on its application). By the analysis of enactments on amnesty and a process of their adoption, transcripts of the Russian State Duma sessions, as well as selected judgments, the author ascertains possible and real problems determined by the mentioned form of amnesty (misinterpretation of enactments, a delay in adopting and in entering into legal force of the enactment on amnesty and the enactment on its application). The author concludes that it is necessary to regulate all aspects of amnesty by a unified enactment. Besides that, the author proposes some other ways to eliminate the problems (united voting for the draft enactment on amnesty and the draft enactment on its application at the third reading, strict distribution of certain provisions between two enactments).